The Impact of the Coronavirus Disease 2019 Pandemic on Investor Sentiment—Evidence From A-Share Listed Companies in China - Song, Yuegang; Hao, Xiazhen; Lu, Zhou (Frontiers in Psychology, 2021)
In a difference-in-difference model (DID), this paper studies the impact of the COVID-19 pandemic on the investor sentiment in China’s financial market using monthly panel data on newly listed Chinese companies between October 2019 and June 2020. The outbreak of the pandemic is shown to exert a significantly negative impact on investor sentiment. A future industry heterogeneity analysis shows that the pandemic has driven up investor sentiment in pharmaceutical sector while having a significantly negative impact on non-pharmaceutical sectors. The pandemic is shown to have a negative impact on China’s private sector and foreign-invested sector while a significantly positive impact on the state-owned sector. This paper contributes to the existing literature on the investigation of how significant the impact of public health emergencies on investor sentiment is.